Inequalities in adherence to the continuum of maternal and child health service utilization in Ethiopia: multilevel analysis - Nigatu Regassa Geda; Cindy Xin Feng; Carol J. Henry; Rein Lepnurm; Bonnie Janzen; Susan J. Whiting (BMC, 2021)
Abstract Background Despite progress made to improve access to child health services, mothers' consistent utilization of these services has been constrained by several factors. This study is aimed at assessing the inequalities in key child health service utilization and assess the role of antenatal care (ANC) on subsequent service use. Method The analysis of the present study was based on the Ethiopian Demographic and Health Surveys, a nationally representative sample of 10,641 children. A health service utilization score was constructed from the affirmative responses of six key child health interventions associated with the most recent birth: ANC service, delivery of the last child at health facilities, postnatal care services, vitamin A intake, iron supplementation and intake of deworming pills by the index child. A mixed effect Poisson regression model was used to examine the predictors of health service utilization and three separate mixed effect logistic regression models for assessing the role of ANC for continued use of delivery and postnatal care services. Results The results of mixed effect Poisson regression indicate that the expected mean score of health service utilization was lower among non-first birth order children, older and high parity women, those living in polygamous families and women living in households with no access to radio. The score was higher for respondents with better education, women who had previous experience of terminated pregnancy, residing in more affluent households, and women with experiences of mild to high intimate partner violence. Further analysis of the three key health services (ANC, delivery, and postnatal care), using three models of mixed effect logistic regression, indicates consistent positive impacts of ANC on the continuum of utilizing delivery and postnatal care services. ANC had the strongest effects on both institutional delivery and postnatal care service utilization. Conclusion The findings implicated that maternal and child health services appear as continuum actions/behavior where utilization of one affects the likelihood of the next service types. The study indicated that promoting proper ANC services is very beneficial in increasing the likelihood of mothers utilizing subsequent services such as delivery and postnatal care services.